2023
DOI: 10.3389/fnagi.2023.1252610
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced brain functional connectivity and activation after 12-week Tai Chi-based action observation training in patients with Parkinson’s disease

Lin Meng,
Deyu Wang,
Yu Shi
et al.

Abstract: IntroductionMotor-cognitive interactive interventions, such as action observation training (AOT), have shown great potential in restoring cognitive function and motor behaviors. It is expected that an advanced AOT incorporating specific Tai Chi movements with continuous and spiral characteristics can facilitate the shift from automatic to intentional actions and thus enhance motor control ability for early-stage PD. Nonetheless, the underlying neural mechanisms remain unclear. The study aimed to investigate ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Specifically in the resting state, this technique, known as functional connectivity, shows promise for identifying early PD-related changes in brain activity [ 26 ]. Research [ 27 ] showed that using changes in functional connectivity within the basal ganglia network, resting-state fMRI could accurately distinguish early-stage PD patients from healthy controls with 91.7% accuracy.…”
Section: Reviewmentioning
confidence: 99%
“…Specifically in the resting state, this technique, known as functional connectivity, shows promise for identifying early PD-related changes in brain activity [ 26 ]. Research [ 27 ] showed that using changes in functional connectivity within the basal ganglia network, resting-state fMRI could accurately distinguish early-stage PD patients from healthy controls with 91.7% accuracy.…”
Section: Reviewmentioning
confidence: 99%